Large Enchondroma of Metacarpal Bone with Pathological Fracture Treated with Marginal Resection and Reconstruction with Iliac Crest Graft: A Rare Case Report - Pandey, Suresh (Journal of College of Medical Sciences-Nepal, 2019)
Enchondroma is the benign bone tumor commonly found in phalanx and metacarpal shaft. The most common method of treatment is curettage with or without filling cavity with bone graft with recurrence rate up to 13%. We present a large enchondroma of fourth metacarpal right hand with cortical breach treated with marginal excision and reconstruction of segmental defect with tricortical iliac crest bone graft with excellent functional and cosmetic result. We opted to report this case because of the large size of the tumor and successful reconstruction of metacarpal with simple technique of autograft.